Effects of Chikungunya virus immunity on Mayaro virus disease and epidemic potential - Webb, Emily M. (Sci Rep, 2019)
Mayaro virus (MAYV) causes an acute febrile illness similar to that produced by chikungunya virus (CHIKV), an evolutionary relative in the Semliki Forest virus complex of alphaviruses. MAYV emergence is typically sporadic, but recent isolations and outbreaks indicate that the virus remains a public health concern. Given the close phylogenetic and antigenic relationship between CHIKV and MAYV, and widespread distribution of CHIKV, we hypothesized that prior CHIKV immunity may affect MAYV pathogenesis and/or influence its emergence potential. We pre-exposed immunocompetent C57BL/6 and immunocompromised A129 or IFNAR mice to wild-type CHIKV, two CHIKV vaccines, or a live-attenuated MAYV vaccine, and challenged with MAYV. We observed strong cross-protection against MAYV for mice pre-exposed to wild-type CHIKV, and moderately but significantly reduced cross-protection from CHIKV-vaccinated animals. Immunity to other alphavirus or flavivirus controls provided no protection against MAYV disease or viremia. Mechanistic studies suggested that neutralizing antibodies alone can mediate this protection, with T-cells having no significant effect on diminishing disease. Finally, human sera obtained from naturally acquired CHIKV infection cross-neutralized MAYV at high titers in vitro. Altogether, our data suggest that CHIKV infection can confer cross-protective effects against MAYV, and the resultant reduction in viremia may limit the emergence potential of MAYV.